2017
DOI: 10.1038/s41598-017-05713-2
|View full text |Cite
|
Sign up to set email alerts
|

Viral driven epigenetic events alter the expression of cancer-related genes in Epstein-Barr-virus naturally infected Burkitt lymphoma cell lines

Abstract: Epstein-Barr virus (EBV) was identified as the first human virus to be associated with a human malignancy, Burkitt’s lymphoma (BL), a pediatric cancer endemic in sub-Saharan Africa. The exact mechanism of how EBV contributes to the process of lymphomagenesis is not fully understood. Recent studies have highlighted a genetic difference between endemic (EBV+) and sporadic (EBV−) BL, with the endemic variant showing a lower somatic mutation load, which suggests the involvement of an alternative virally-driven pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 55 publications
4
29
0
Order By: Relevance
“…Our comparative analysis of the whole genome methylation profiles of a set of EBV (+) and EBV (-) Burkitt’s lymphoma derived cell lines (4), led to identification of two CpGs (CpG 15695155 and 21423404) in an intragenic putative regulatory region of KDM2B (Fig 1A) highly methylated in EBV (+) BL derived cells. To validate these data we performed direct pyrosequencing on DNA extracted from 7 BL EBV (+) BL and 7 EBV (-) BL derived cell lines and confirmed that KDM2B gene is hyper-methylated at CpG 15695155 and 21423404 in EBV (+) BL cell lines compared to EBV (–) BL cell lines (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our comparative analysis of the whole genome methylation profiles of a set of EBV (+) and EBV (-) Burkitt’s lymphoma derived cell lines (4), led to identification of two CpGs (CpG 15695155 and 21423404) in an intragenic putative regulatory region of KDM2B (Fig 1A) highly methylated in EBV (+) BL derived cells. To validate these data we performed direct pyrosequencing on DNA extracted from 7 BL EBV (+) BL and 7 EBV (-) BL derived cell lines and confirmed that KDM2B gene is hyper-methylated at CpG 15695155 and 21423404 in EBV (+) BL cell lines compared to EBV (–) BL cell lines (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence argues that different viruses may abrogate cellular defense systems by hijacking epigenetic mechanisms to deregulate host cell gene expression program and modulate their own life cycle (2, 3). Our recent study of the methylome profiles of sporadic- versus endemic-derived BL cell lines revealed EBV infection-specific pattern of methylation, with aberrant methylation in genes with a known role in lymphomagenesis, such as ID3, often found mutated in sporadic BL (sBL) (4). We therefore hypothesized that a viral-driven mechanism is responsible for modifying the epigenome of B-cells to facilitate the lymphomagenic process, circumventing the need for mutations in lymphoma driver genes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, impairing mutations in repressive function of ID3 results in B‐cell signaling activation and lymphoid proliferation . In 2017, a published study revealed that LMP1 promotes promoter methylation and silencing of ID3 expression via enhancing recruitment of the DNMTs during the EBV infection in B cells . Paschos and colleagues attempted to display the relation between EBV latency and suppression of tumor suppressor gene Bim.…”
Section: Epstein‐barr Virusmentioning
confidence: 99%
“…Epstein-Barr virus (EBV) was the first human virus that was found to be associated with a variety of human malignancies with origin of lymphoid or epithelial including Burkitt's lymphoma (BL), nasopharyngeal carcinoma (NPC), gastric carcinoma (GC), posttransplant lymphoproliferative disease (PTLD), and Hodgkin's lymphoma (HL). 44,45 Pathogenesis of EBV-associated cancers (EBVaC) seems to be correlated with role of the virus as a direct epigenetic driver. 46,47 EBV encodes two latent phase proteins named LMP-1 and LMP-2 that are considered as oncogenic elements with crucial role in tumor transformation that affect epithelial and lymphoid cells.…”
Section: Epstein-barr Virusmentioning
confidence: 99%
See 1 more Smart Citation